Pressupostos para uma justiça social na Suma de Teologia de Tomás de Aquino - Felici, Antônio Ilário (2017)
The present research of philosophy deals with the presuppositions of social justice in the Summa of Theology of Thomas Aquinas in question 58 about the justice. It begins the reflection by a study of the Summa as contextualization of the subject. The study of the Summa of Theology, even in its form, allows us to understand its content as a manual of catholic doctrine for students of theology, the point of arrival of the author's theological thought, but a starting point for further study, a task assumed by the present study. Thus, it examines the articles of the question, the author's related writings and their sources in other authors as foundations for social justice, especially those that are most inclined to that direction, such as general or legal, distributive and commutative justice. Based on these bases, the research intends to infer what can be said of social justice in Thomas Aquinas